Rheumatoid Arthritis Complicated with Nasal Septum Perforation Due to Methotrexate-associated Lymphoproliferative Disorder - Sakaguchi, Ryuki (Intern Med, 2019)
A 44-year-old female with rheumatoid arthritis treated with methotrexate (MTX) and tocilizumab (TCZ) was admitted to our hospital with nasal pain. Nasal fiberscopy revealed septum perforation, while a membrane biopsy indicated granuloma and fibrinoid necrosis of the small artery. The patient was treated with prednisolone 30 mg/day after discontinuation of MTX and TCZ. Inguinal lymph node biopsy revealed diffuse infiltrations of atypical T-cells and Epstein-Barr virus-positive B cells. The patient was diagnosed with peripheral T-cell lymphoma due to MTX-associated lymphoproliferative disorder (MTX-LPD). We herein describe the case of a patient with nasal septum perforation due to MTX-LPD mimicking granulomatosis with polyangiitis.